Cu2+-mediated complex formation between polyacrylic acid (PAA) and bovine serum albumin - (:unkn) unknown (ELSEVIER SCIENCE BV, 1996)
Cu2+-mediated complex formation between polyacrylic acid (PAA) and negatively charged bovine serum albumin (BSA) was studied in neutral water in the presence of Cu2+. Depending on the concentration of Cu2+, the reaction between PAA-Cu2+ complexes and BSA appeared to follow one of two possible paths. At low Cu2+ concentrations (n(Cu)/n(AA) < 0.15), a further increase in BSA concentration led to the breakdown of the complex as in mechanism I: [GRAPHICS] At higher Cu2+ concentrations (n(Cu)/n(AA) > 0.15), a further increase in BSA concentration led to the formation of non-stoichiometric polycomplexes (mechanism II): [GRAPHICS] The immunogenic properties of ternary mixtures of BSA-Cu2+-PAA were investigated and the relationship between immunogenicity and complex formation in solution was analyzed. The addition of Cu2+ to solutions of PAA with BSA gave rise to a considerable increase in BSA-specific immunogenicity. Data obtained from the analysis of the immunogenicity of BSA-Cu2+-PAA mixtures formed using different ratios of the components suggested that (1) the highest immunogenic activity is exhibited by stable ternary complexes, and (2) immunoactive polyelectrolyte complexes have a non-stoichiometric composition. We thus propose a novel method, based on Cu2+ mediated complex formation, to enhance protein-specific antibody responses.
Keywords: polyelectrolyte; ternary polyelectrolyte complex; immunization; antibody response